The Efforts to Increase Teacher's Competence in Online Learning Through Megicom Workshop During The Covid -19 Pandemic - Aidawati Aidawati (FKIP UNIVERSITAS PAKUAN, 2022)
This research aims ro improve teacher`s competence in online learning through Megicom Workshop during the Covid-19 pandemic in the 2020/2021 academic year of SMA Negeri 9 Bogor. This research was conducted in two cycles with 45 teachers in SMA Negeri 9 Bogor. The research was carried out for 5 (five) months, namely July – November 2020. Based on the reasearch results, after going through the Digital Media Competency Workshop, the competence of teachers in carrying out synchronous online learning has increased. From the results of observations through academic supervision, it was found that in cycle 1, as many as 38% were very good in carrying out online learning activities in the classroom, 49% were good, and 13% were quite good in carrying out online learning activities in the classroom. While in cycle 2, 49% were very good in carrying out synchronous online learning activities, 51% were good, and there was no longer sufficient category). The competence of teachers in implementing synchronous online learning has increased. The results showed that in cycle 1, as many as 42% were very good at carrying out synchronous online learning activities, 47% were good, and 11% were quite good in implementing asynchronous learning activities. While in cycle 2, 60% were very good in carrying out asynchronous online learning activities, 40% were good, and there was no longer sufficient category. The average value of supervision results in synchronous classroom management, has increased from 85.14 to 87.64. Meanwhile, the average value of supervision results in asynchronous classroom management has increased from 85.06 to 87.47. The competence of teachers in the use of digital media has increased, after participating in the Megicom Workshop. This can be seen from the increasingly varied media used, such as Google Classroom, WhatsApp, Quizizz, Google Meet, Zoom Meeting, Instagram, and YouTube. It could be be concluded that the competence of teachers in online learning during the Covid -19 pandemic at SMA Negeri 9 Bogor for the 2020/2021 academic year could be improved through the Megicom Workshop.